La recherche comme partage. Compte-rendu de La recherche en contexte de vulnérabilité – engagement du chercheur et enjeux éthiques, sous la direction de Nathalie Mondain et Arzouma Éric Bologo - Des Rosiers, Brigitte (BioéthiqueOnline, 2013)
La recherche en contexte de vulnérabilité – engagement du chercheur et enjeux éthiques, edited by Nathalie Mondain and Arzouma Eric Bologo, presents a series of lucid articles and valuable lessons about the limits of a rigid application, in the field, of a priori methodological and research ethics procedures. The authors suggest that these limits may be countered by the participation of all stakeholders in the in situ co-construction of a project, ensuring its relevance and validity.